PV system with maximum power point tracking: modeling, simulation and experimental results - Melício, Rui (2014)
This paper focuses on the photovoltaic cell five parameters modeling, consisting on a current controlled generator, single-diode, a shunt and series resistances. An identification of the parameters for a photovoltaic system supported the maximum power point tracking implementation based on dP/dV . The identification of parameters and the performance obtained with the equivalent circuit model for a solar module are validated by data measured on an in sitú photovoltaic system.